Recurrent loops: Incorporating prediction error and semantic/episodic theories into Drosophila associative memory models. (5th April 2019) - Horiuchi, Junjiro
Abstract : In 2003, Martin Heisenberg et al. presented a model of how associative memories could be encoded and stored in the insect brain. This model was extremely influential in the Drosophila memory field, but did not incorporate several important mammalian concepts, including ideas of separate episodic and semantic types of memory and prediction error hypotheses. In addition, at that time, the concept of memory traces recurrently entering and exiting the mushroom bodies, brain areas where associative memories are formed and stored, was unknown. In this review, I present a simple updated model incorporating these ideas, which may be useful for future studies. Abstract : A model of Drosophila associative memory incorporating prediction error hypotheses and episodic/semantic memory forms.